Artificial Intelligence (AI) and Machine Learning: The Future of Information Technology and Information Systems - A. Aviv Mahmudi; Iyan Ramadhani (Penelitian dan Pengembangan Ilmu, 2024)
In the context of data and information management in large organizations, the integration of Artificial Intelligence (AI) and Machine Learning (ML) technology is an interesting research subject. This research aims to investigate the benefits, challenges and findings related to the use of this technology. Through a systematic literature review approach, the analysis results show that the integration of AI and ML has great potential to increase efficiency, productivity and innovation in large organizations in various industrial sectors. However, the research also identified challenges that need to be overcome, such as technical complexity, data security issues, and ethical considerations. The implications of this research highlight the importance of awareness of effective risk management and the development of appropriate strategies to optimize the benefits of AI and ML technologies while minimizing their risks and negative impacts. Overall, the integration of AI and ML is a promising area for further research, with the potential to provide significant positive impact for large organizations in this digital era.